Transcriptomic and Weighted Gene Co-expression Correlation Network Analysis Reveal Resveratrol Biosynthesis Mechanisms Caused by Bud Sport in Grape Berry - Leng, Feng; Ye, Yunling; Zhou, Jialing; Jia, Huijuan; Zhu, Xiaoheng; Shi, Jiayu; Zhang, Ziyue; Shen, Nan; Wang, Li (Frontiers in Plant Science, 2021)
Resveratrol is a natural polyphenolic compound in response to biotic and abiotic stresses in grape berries. However, resveratrol changes caused by bud sport are scarce and not conclusive. In our studies, trans-resveratrol and cis-resveratrol were identified and quantified in the grape berries of ‘Summer Black’ and its bud sport ‘Nantaihutezao’ from the veraison to ripening using Ultra Performance Liquid Chromatography-high resolution tandem Mass Spectrometry (UPLC-HRMS). We found bud sport accumulates the trans-resveratrol earlier, and increases the cis-resveratrol contents in the earlier stages but decreases its contents in the later stages. Simultaneously, we used RNA-seq to identify 51 transcripts involved in the stilbene pathways. Particularly, we further identified 124 and 19 transcripts negatively correlated with trans-resveratrol and cis-resveratrol contents respectively, and 4 transcripts encode F3’5’H positively correlated with trans-resveratrol contents by weighted gene co-expression network analysis (WGCNA). These transcripts may play important roles in relating to the synergistic regulation of resveratrol metabolisms.